Análise do risco ambiental em rios mediante aplicação de um modelo matemático bidimensional difuso considerando a influência de ondas de cheia - Araújo, Juliana Alencar Firmo de (2015)
The presence of physical, chemical and biological components in rivers, associated with fluvial dynamics in these ecosystems, enables the existence of extremely c omplex processes, making your description using mathematical models a challenging task. This implies the need to establish a set of insightful simplifications, in order to get results that may describe these processes with a degree of realism. The use of m athematical models to evaluate the release and assimilation of polluting matters into a water body is a most important tool, due to complexity of the determining processes on issues of water quality. These models are based on the fundamentals of mass conse rvation principle amongst Fick's law for polluting transport. On the other hand, this type of analysis generate deterministic models where there is no possibility to evaluate the inherent uncertainties in various phenomena developed in water bodies. To ove rcome these drawbacks, some research has made use of a methodology based on fuzzy theory. This theory is based on mathematical representation of some parameters in the form of membership functions, and has the advantage of allowing an assessment of uncerta inty in any physical process, without the need of a database so consistent. This work aims to analyze the relations among pollutant concentration and transient flow fields compound by flood waves in natural rivers, through the application of a two - dimensional model of mass transport, in its fuzzy form, so that fields of environmental risk may be studied. To achieve the goals, the differential equations of mass transport, as well as the hydrodynamics equations, were treated in its fuzzy forms and solved by applying the finite difference method. The results were obtained using a computer program in FORTRAN language, allowing the achievement of various simulations for different scenarios. T he results indicated that the presence of diffused wave in the transport models have a very different behavior of the kinematic wave model, thus showing that more detailed studies are needed to reach definitive conclusions for these problems related to wat er quality.